The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)

The European carbon balance. Part 2: croplands - P. CIAIS; M. WATTENBACH; N. VUICHARD; P. SMITH; S. L. PIAO; A. DON; S. LUYSSAERT; I. A. JANSSENS; A. BONDEAU; R. DECHOW; A. LEIP; PC. SMITH; et al. (Global Change Biology, 2010)
We estimated the long‐term carbon balance [net biome production (NBP)] of European (EU‐25) croplands and its component fluxes, over the last two decades. Net primary production (NPP) estimates, from different data sources ranged between 490 and 846 gC m −2 yr −1 , and mostly reflect uncertainties in allocation, and in cropland area when using yield statistics. Inventories of soil C change over arable lands may be the most reliable source of information on NBP, but inventories lack full and harmonized coverage of EU‐25. From a compilation of inventories we infer a mean loss of soil C amounting to 17 g m −2 yr −1 . In addition, three process‐based models, driven by historical climate and evolving agricultural technology, estimate a small sink of 15 g C m −2 yr −1 or a small source of 7.6 g C m −2 yr −1 . Neither the soil C inventory data, nor the process model results support the previous European‐scale NBP estimate by Janssens and colleagues of a large soil C loss of 90 ± 50 gC m −2 yr −1 . Discrepancy between measured and modeled NBP is caused by erosion which is not inventoried, and the burning of harvest residues which is not modeled. When correcting the inventory NBP for the erosion flux, and the modeled NBP for agricultural fire losses, the discrepancy is reduced, and cropland NBP ranges between −8.3 ± 13 and −13 ± 33 g C m −2 yr −1 from the mean of the models and inventories, respectively. The mean nitrous oxide (N 2 O) flux estimates ranges between 32 and 37 g C Eq m −2 yr −1 , which nearly doubles the CO 2 losses. European croplands act as small CH 4 sink of 3.3 g C Eq m −2 yr −1 . Considering ecosystem CO 2 , N 2 O and CH 4 fluxes provides for the net greenhouse gas balance a net source of 42–47 g C Eq m −2 yr −1 . Intensifying agriculture in Eastern Europe to the same level Western Europe amounts is expected to result in a near doubling of the N 2 O emissions in Eastern Europe. N 2 O emissions will then become the main source of concern for the impact of European agriculture on climate.

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)
Overviewing the European carbon (C), greenhouse gas (GHG), and non‐GHG fluxes, gross primary productivity (GPP) is about 9.3 Pg yr −1 , and fossil fuel imports are 1.6 Pg yr −1 . GPP is about 1.25% of solar radiation, containing about 360 × 10 18 J energy – five times the energy content of annual fossil fuel use. Net primary production (NPP) is 50%, terrestrial net biome productivity, NBP, 3%, and the net GHG balance, NGB, 0.3% of GPP. Human harvest uses 20% of NPP or 10% of GPP, or alternatively 1‰ of solar radiation after accounting for the inherent cost of agriculture and forestry, for production of pesticides and fertilizer, the return of organic fertilizer, and for the C equivalent cost of GHG emissions. C equivalents are defined on a global warming potential with a 100‐year time horizon. The equivalent of about 2.4% of the mineral fertilizer input is emitted as N 2 O. Agricultural emissions to the atmosphere are about 40% of total methane, 60% of total NO‐N, 70% of total N 2 O‐N, and 95% of total NH 3 ‐N emissions of Europe. European soils are a net C sink (114 Tg yr −1 ), but considering the emissions of GHGs, soils are a source of about 26 Tg CO 2 C‐equivalent yr −1 . Forest, grassland and sediment C sinks are offset by GHG emissions from croplands, peatlands and inland waters. Non‐GHGs (NH 3 , NO x ) interact significantly with the GHG and the C cycle through ammonium nitrate aerosols and dry deposition. Wet deposition of nitrogen (N) supports about 50% of forest timber growth. Land use change is regionally important. The absolute flux values total about 50 Tg C yr −1 . Nevertheless, for the European trace‐gas balance, land‐use intensity is more important than land‐use change. This study shows that emissions of GHGs and non‐GHGs significantly distort the C cycle and eliminate apparent C sinks.